Thoughts painfully intense : Hawthorne and the invalid author - Mancall, James N., 1964- (New York : Routledge, 2002)
First Published in 2002. Routledge is an imprint of Taylor & Francis, an informa company.
Fanshawe, the alma mater and the invalid author -- Tremulous hands and devil's claws : short fiction -- Pure hands and witchcraft -- Out of dream-land : the Blithedale romance -- Secret histories and silences -- Haunted quacks and neutral territories.
Based on the author's thesis (Ph. D.).
Includes bibliographical references (pages 135-140) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Hawthorne, Nathaniel, -- 1804-1864 -- Knowledge -- Medicine; Hawthorne, Nathaniel, -- 1804-1864 -- Characters -- Authors; Hawthorne, Nathaniel, -- 1804-1864; Hawthorne, Nathaniel, -- 1804-1864; Hawthorne, Nathaniel; Literature and medicine -- United States -- History -- 19th century; Authorship -- Psychological aspects; Authors -- Health and hygiene; Mind and body in literature; Authorship in literature; Invalids in literature; Medicine in literature; Literature and morals; Authors in literature; Body and soul in literature; Authorship; Medicine in Literature; Authorship; Disease -- psychology; Literature, Modern; Littérature et médecine -- États-Unis -- Histoire -- 19e siècle.; Art d'écrire -- Aspect psychologique; Écrivains -- Santé et hygiène.; Esprit et corps dans la littérature.; Art d'écrire dans la littérature.; Personnes handicapées dans la littérature.; Médecine dans la littérature.; Littérature et morale; Écrivains dans la littérature.; Art d'écrire.; authorship; LITERARY CRITICISM -- American -- General; Body and soul in literature; Authorship; Authors -- Health and hygiene; Authors in literature; Authorship in literature; Authorship -- Psychological aspects; Invalids in literature; Literature and medicine; Literature and morals; Medicine; Medicine in literature; Mind and body in literature; United States; Körperbehinderung; 1800-1899; History